Effect of Weight-Bearing in Conservative and Operative Management of Fractures of the Base of the Fifth Metatarsal Bone. (26th December 2017) - Park, Jae-Yong; Kim, Hyong-Nyun; Hyun, Yoon-Suk; Park, Jun-Sik; Kwon, Hwan-Jin; Kang, Sae-Hyun; Kim, Gab-Lae
Abstract : Background . There is no established principle regarding weight-bearing in conservative and operative management of fifth metatarsal base fractures. Methods . We reviewed 86 patients with acute fifth metatarsal base fractures. Conservatively treated late or early weight-bearing patients were assigned to Group A or C, respectively. Operatively treated late or early weight-bearing patients were assigned to Group B or D, respectively. Results were evaluated by clinical union, bone resorption, and the American Orthopaedic Foot and Ankle Society (AOFAS) and Visual Analogue Scale (VAS) scores. Results . All 4 groups had bone union at a mean of 6.9 weeks (range, 5.1–15.0). There were no differences between the groups in the AOFAS and VAS scores. In the early weight-bearing groups, there were fewer cases of bone resorption, and the bone unions periods were earlier. Conclusions . Early weight-bearing may help this patient population. Moreover, conservative treatment could be an option in patients with underlying diseases.